Research Letter: Performance of the Brief Test of Adult Cognition by Telephone in a National Sample. Issue 4 (22nd July 2021) - DiBlasio, Christina A.; Sima, Adam; Kumar, Raj G.; Kennedy, Richard E.; Retnam, Reuben; Lachman, Margie E.; Novack, Thomas A.; Dams-O'Connor, Kristen
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To create a larger, more representative community comparison sample of the Brief Test of Adult Cognition by Telephone (BTACT) data to facilitate assessment of cognitive function in research studies. Setting: National US community-based survey. Participants: In total, 6747 healthy adults aged 23 to 84 years (53% female; mean age = 55 years, SD = 13). Design: Secondary data analysis of BTACT data collected from the National Survey of Midlife Development in the United States (MIDUS) II and MIDUS Refresher cohorts. Main Measures: The BTACT, a brief (15-20 minute) measure of global cognitive function validated for telephone administration. Results: This article provides BTACT community comparison sample data based on age, sex, and education from a national sample. Similar to other cognitive measures, BTACT scores decreased with age and increased with education. Conclusions: The BTACT community comparison sample will facilitate investigation of cognitive functioning in large-scale traumatic brain injury research studies and will support secondary analysis of existing BTACT data gathered through the MIDUS study.